Laparoscopic parastomal herniorrhaphy utilizing transversus abdominis release and a modified Sugarbaker technique: A case report. Issue 1 (3rd June 2020) - Imamura, Kiyotaka; Takada, Minoru; Umemoto, Kazufumi; Furukawa, Shotaro; Ambo, Yoshiyasu; Nakamura, Fumitaka
Abstract: A 69‐year‐old woman was referred to our department with complaints of abdominal discomfort in the standing position. She had undergone robot‐assisted radical cystectomy and ileal conduit urinary diversion for bladder cancer 10 months earlier. Abdominal CT revealed a parastomal hernia. Laparoscopic parastomal hernia repair using the Pauli technique was performed successfully with no recurrence after a 4‐month follow‐up. Although there are concerns about potential mesh‐related complications and long‐term results, this novel approach can be a successful option for parastomal hernia repair. As far as we know, this is the first English‐language report on the application of Pauli parastomal hernia repair combined with a pure laparoscopic approach.